The time of flight method applied to 2.37 MeV neutrons. - Hsu, Tung-Hong. (University of Ottawa (Canada), 1964)
A time of flight system using an associated particle detector was developed for use with DD neutrons of 2.37 MeV. As part of this system a new method of neutron gamma discrimination based on the Owen principle was developed; this method distinguishes 0.5 MeV neutrons from a very wide energy range of gamma rays. This apparatus was then used to measure the angular distributions of the neutrons scattered from the ground state and the 0.845 MeV state of Fe56.
Keywords: Physics, Nuclear.